Supramolecular derivatisation of new anti-tubercular and antimalarial drug leads - Joseph, Laurelle Margaux (Department of Chemistry, 2016)
The UCT Drug Discovery and Design Centre, H3D, provided anti-tubercular and antimalarial drug leads that display potent in vitro and in vivo activity, but with unfavourable physicochemical properties. The primary objective of this study was to prepare supramolecular derivatives of the drug leads in an attempt to improve their physicochemical properties. Any new solid forms were to be characterized by a variety of analytical techniques, including X-ray analysis, spectroscopic and thermal techniques. Where possible, such derivatives would be tested for any enhancement in the aqueous solubility or biological activity of the drug lead. The second objective of this study was to employ supramolecular intervention in the early stages of the drug discovery and development process to help streamline the process by distinguishing between compounds that might be amenable to beneficiation via supramolecular modification and those that might not. The crystal structure of a novel anti-tubercular drug lead, DL2, was solved and the compound was fully characterized using thermal and X-ray techniques. This compound displayed very poor solubility in both aqueous and organic media. Phase solubility studies were performed with anti-tubercular drug lead DL3 and selected cyclodextrins (CDs). The apparent solubility of DL3 increased by a factor of more than 300 at the highest concentration of hydroxypropyl-β-CD (HPβCD) and β-CD investigated. Three salts of antimalarial drug lead DL4 and carboxylic acids were prepared. The salts were characterized by X-ray and thermal techniques. A salt of citric acid and DL4 could be prepared by the liquid-assisted grinding method. The equilibrium solubility of this salt was 48 times greater than that of DL4.